2016
DOI: 10.3892/mmr.2016.5099
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet-associated proteins in atherosclerosis (Review)

Abstract: Accumulation of atherosclerotic plaques in arterial walls leads to major cardiovascular diseases and stroke. Macrophages/foam cells are central components of atherosclerotic plaques, which populate the arterial wall in order to remove harmful modified low-density lipoprotein (LDL) particles, resulting in the accumulation of lipids, mostly LDL-derived cholesterol ester, in cytosolic lipid droplets (LDs). At present, LDs are recognized as dynamic organelles that govern cellular metabolic processes. LDs consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 104 publications
(130 reference statements)
0
29
0
Order By: Relevance
“…Excess accumulation of the free forms of lipids such as free FA and free cholesterol in the ER causes the ER stress response, resulting in cellular apoptosis and necrosis [ 48 , 49 ]. Therefore, the ER converts the surplus of cytotoxic free forms of lipids into neutral forms (e.g., TG and sterol esters), which in turn are stored in cytosolic lipid droplets (LDs) [ 4 ].…”
Section: Applications Of Lipidomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess accumulation of the free forms of lipids such as free FA and free cholesterol in the ER causes the ER stress response, resulting in cellular apoptosis and necrosis [ 48 , 49 ]. Therefore, the ER converts the surplus of cytotoxic free forms of lipids into neutral forms (e.g., TG and sterol esters), which in turn are stored in cytosolic lipid droplets (LDs) [ 4 ].…”
Section: Applications Of Lipidomicsmentioning
confidence: 99%
“…Lipids function as an energy reservoir and serve as major structural components of biological membranes such as plasma membranes, membranes of intracellular organelles, and lipid transporters [ 3 ]. Lipids also participate in signal transduction as chemical messengers and interact with proteins to regulate their functions [ 4 , 5 ]. Furthermore, lipids are important bioactive molecules in the body’s immune system against viral and bacterial infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, sPLA 2 s from Bothrops snake venoms share structural and functional features with mammalian inflammatory GIIA sPLA 2 s, which are found in high concentrations in inflammatory exudates [ 3 , 4 ]. Our group has previously demonstrated that an Asp49 sPLA 2 , named myotoxin-III (MT-III), isolated from Bothrops asper snake venom, activates inflammatory functions of macrophages, including formation of lipid droplets (LDs) and upregulation of perilipin 2 (PLIN2), a scaffold protein involved in LD assembly and macrophage differentiation into foam cells [ 5 7 ]. However, the mechanisms involved in foam cell formation induced by sPLA 2 MT-III are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LDs are cytoplasmic organelles, present in high levels in foam cells, that are comprised by a hydrophobic core of neutral lipids (triglycerides and cholesterol esters) surrounded by a phospholipid monolayer and a growing list of associated proteins [ 7 9 ]. LDs are found in inflammatory leukocytes and described as rich deposits of esterified arachidonic acid (AA), a precursor of eicosanoids, and enzymes necessary for their synthesis, including cyclooxygenases (COX) and prostaglandin E 2 synthase [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is one of the most common causes of cardiovascular disease, which is characterized by subsequent myocardial ischemia, insufficient blood supply to the coronary arteries and hypoxia ( 3 , 4 ). Atherosclerosis characterized by lipid deposition is the most common and important type of arteriosclerosis in the intima of the involved artery, proliferation of fibrous tissue, calcium deposition, lesions in the middle layer of the artery and accumulation of complex carbohydrates ( 5 ). Clinically, coronary heart disease is a fundamental pathological phenotype of atherosclerosis ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%